The Effectiveness of Tax Planning for Natural Costs to Company Employees as an Effort for Tax Efficiency - Tiara Indira Soegandhi; Amanda Yeselin (Golden Ratio of Taxation Studies, 2021)
The purpose of this research is to find out how far tax planning for in-kind expenses can make the tax burden on PT. Karsa Makassar land. This type of research is descriptive. Data obtained by using interview documentation. Data analysis uses a qualitative approach. The results of the study show that tax planning for in-kind expenses for company employees can streamline the amount of tax owed by the company by recognizing in-kind costs as the company's operational expenses. PT management Bumi Karsa Makassar should apply tax planning for in-kind costs in streamlining the company's operations.